Dens evaginatus in association with necrotic pulp and periapical abscess in a 13-year-old girl - Kusumawardani, Anisa; Ardini, Yunita Dewi; Hasan, Taufiq Hidayat (2016)
Introduction: Dens evaginatus (DE) is an uncommon dental anomaly, where an extra cusp or tubercle protrudes from the occlusal surface of posterior teeth, as well as the lingual surface of anterior teeth. Tubercles are susceptible to pulp exposure from wear or fracture, because of malocclusion, leading to pulpal complications early after eruption. DE most commonly affects premolars; mandibular premolars are five times more frequent than maxillary premolars. Case report: A 13-year-old girl presented to IIUM dental polyclinic with sinus track at the posterior lower left buccal gingiva since 1 year ago. The tooth 35 was sound. At the lingual side there was supernumerary tooth seen in close relation to tooth 35. Electric pulp test showed that tooth 35 already non vital. Intra-oral periapical radiograph and cone beam computed tomography scan showed an abnormal-appearing root which correspond to DE type III with radiolucency at the periapical area. Root canal treatment was performed using crown down pressureless technique and obturation was done using lateral condensation technique. The tooth was restored using composite restoration. Comments: DE is an uncommon condition. It is reported in Asian population with varying estimates at 0.5 to 4.3%, depend on the population group studied. It is quite a challenge for dental practitioner since the diagnosis is difficult and the treatment options are limited. In the case of DE with necrotic pulp and periapical abscess, root canal treatment can be a treatment of choice. It shows high success rate if it is followed by adequate restoration.